Effects of interleukin-12/23 inhibitors and interleukin-17 inhibitors on myocardial functions in patients with severe psoriasis - Leyla Baykal Selçuk; Mursel Şahin; Burcu Aydemir; Deniz Aksu Arıca; Savaş Yaylı (Turkderm Turkish Archives of Dermatology and Venereology)
Background and Design: Systemic inflammation, which is involved in the pathogenesis of psoriasis, has been associated with the development of systemic diseases such as metabolic syndrome and cardiovascular disease. Without prospective data, the relationship between biological therapies and myocardial function in patients with severe psoriasis remains unclear. This study aimed to evaluate myocardial function changes through various parameters in psoriasis patients undergoing biological therapy for 12 months. Materials and Methods: Patients were evaluated at the beginning of treatment and after 12 months using transthoracic echocardiography to assess systolic and diastolic heart functions. Results: A total of 39 patients (20 males, 19 females) with a mean age of 44.28+-13.54 years were included. All treatment groups significantly decreased psoriasis activity and severity index scores after 12 months (p<0.001). No significant changes in biochemical metabolic parameters were observed in any groups during the first year of treatment. A significant improvement in left ventricular global strain was observed in the ustekinumab, secukinumab, and ixekizumab groups compared to baseline (p<0.001, p=0.005, and p<0.001, respectively). A significant improvement in the E/e' ratio was noted in the ustekinumab and ixekizumab groups, but no change was found in the secukinumab group (p=0.017, p=0.010, and p=0.980, respectively). Conclusion: This study observed improvements in systolic and diastolic cardiac functions in patients with severe psoriasis treated with antiinterleukin- 12/23 (IL-12/23) inhibitors and anti-IL-17 therapies.